Domain of applicability of various approaches to description of electromagnetic field in medium - Lyagushyn, S.F.; Sokolovsky, A.I.; Salyuk, Yu.M. (Вопросы атомной науки и техники, 2012)
The problem of parameters, which are necessary for nonequilibrium electromagnetic field description, is investigated on the basis of the Bogolyubov reduced description method establishing the necessity of binary correlations in the minimal set of parameters taken into account in evolution equations. The corresponding theory can be built in terms of one-particle density matrices, Wigner distribution functions, simultaneous correlation functions of field operators, and generating functionals. The obtained results can be analyzed with the help of approaches elaborated in quantum optics. Various methods in theoretical and experimental research into field correlations are compared.